PENGARUH PENGGUNAAN MEDIA CERITA BERGAMBAR DAN AKTIVITAS BELAJAR TERHADAP KEMAMPUAN MENULIS PARAGRAF PADA SISWA KELAS V SDN TANJUNG SETIA PESISIR BARAT - Nurani Nurani (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2019)
The problem that raised in this research is influence of using picture media and learning activities to the ability of writing paragraph. To reach the purpose of the research above, the researcher use correlational methods, it means that the data collected after all the even happen. The techniques to collect the data are analitycal conditional test, statistical analyze, and research hypothesis test. The result of the research showed that (1) there is a positive and significant of using picture media and students’ to ability of writing paragraph with correlation coeffesient is 15,88, (2) there is positive and significant correlation coefficient is 13,70, (3) there is a positive and significant influence of using picture media and learning activities to the ability of writing paragraph is 16,74.